Біологічне забруднення флори Волинської височини видами адвентивних рослин - Stasiuk, M.V.; Glinska, S.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
The aim of the study was to assess the degree of biological contamination of Volhyn Upland flora by species of adventive plants. The content of spontaneous flora consists of 403 species belonging to 253 genera and 75 families. Eukenophytes are represented by 148 species, archeophytes – 116, kenophytes – 139. Stable component mer ges 310 species, unstable – 93. Epecophytes have 241 spe cies, agrioepecophytes – 40, colonophytes – 17, agriophytes – 12, ergaziophytes – 59, ephemerals – 34. North-American and Mediterranean prevail among the adventive plants. Two species are in the species state of expansion. They are Impatiens parviflora DC. and Echinocystis lobata (Michx.) Torr. et Gray. The high invasive ability is found in the species Oenothera biennis L., Acer negundo L., Cichorium intybus L., Sonchus arvensis L., Saponaria officinalis L., Solidago canadensis L., Phalacroloma annuum (L.) Dumort., Heracleum sosnowskyi Manden are transformers.